Defect etching of non-polar and semi-polar faces in SiC - Sakwe, Aloysius; Jang, Yeon-Suk; Wellmann, Peter (Materials Science Forum, 2007)
Wet chemical etching using molten KOH is the most frequently applied method to reveal structural defects in SiC. Until now etching kinetics of SiC in planes different from the polar c-plane has not been reported. In this paper we report on defect etching of SiC in non-polar faces. Using a calibrated KOH defect-etching furnace with possibilities to set accurate etching temperatures we have etched SiC samples of various orientations to (i) study defect occurrence and their morphologies (ii) set KOH defect etching parameters for SiC for these orientations and (iii) investigate etching kinetics in relation to anisotropy/surface polarity. For non-polar planes of the same orientations a comparison in etching kinetics and defect morphologies in crystals grown in different directions is presented.
Keywords: etching; surface polarity; surface potential; activation energy; etching kinetics